Asosiasi Siput Gonggong (Strombus sp.) pada Ekosistem Lamun Di Pesisir Timur Pulau Bintan - Nurul Hati; Ita Karlina; Rika Angraeni; Aditya Hikmat Nugraha; Fadhliyah Idris; Jelita Rahma Hidayati (Universitas Diponegoro, 2022)
The east coast of Bintan Island is an area that has a wide distribution of seagrass with good conditions for the association of Strombus sp in the seagrass ecosystem. This research aims to identify seagrass coverage and abundance of golden snails (Strombus sp) and study the association of golden snails (Strombus sp.) in seagrass ecosystems on the east coast of Bintan Island. This research was conducted on the East Coast of Bintan Island from June until July 2021 (Teluk Bakau Village, Malang Rapat Village and Berakit Village). The tools and materials used in this research were GPS, 1x1 m quadrant transect, roller meter, digital scales, calliper, multitester, hand refractometer, pH meter, pipe (20cm), sieve net, stationery and aluminium foil. The sampling method used three transects with a distance of 100 m towards the sea with a distance between transects of 50 m, with a 1 x 1 m quadrant transect beginning from point 0 until 100 m. Data analysis used in this research were seagrass coverage, Strombus sp. abundance and PCA (Principal Component Analysis) analysis which relates the abundance of barking snails, seagrass cover, water physicochemical parameters and substrate. Strombus sp. found are Strombus urceus, Strombus canarium and Strombus turturella. The Strombus urceus type has a high 4,3 ind/m2 abundance value compared to other types of Strombus sp. at all stations. Types of Strombus canarium and Strombus turturella were mostly found in low seagrass cover and associated with seagrass species Halophila, Thalassia hemprichii and Halodule uninervis, while Strombus urceus species were mostly found in medium and dense seagrass cover and positively associated with Enhalus acoroides, Thallasia hemprichi, Cymodocea rotundata. Pesisir Timur Pulau Bintan merupakan wilayah yang memiliki sebaran lamun yang luas dengan kondisi baik bagi asosiasi Strombus sp. pada ekosistem lamun. Tujuan dari penelitian ini untuk mengidentifikasi tutupan lamun dan kelimpahan siput gonggong (Strombus sp.) dan mempelajari asosiasi siput gonggong (Strombus sp.) pada ekosistem lamun di pesisir Timur Pulau Bintan. Penelitian ini dilakukan di Pesisir Timur Pulau Bintan pada bulan Mei hingga Juni 2021 (Desa Teluk Bakau, Desa Malang Rapat dan Desa Berakit). Alat dan bahan yang digunakan dalam penelitian ini adalah GPS, transek kuadran 1x1 m, rol meter, timbangan digital, jangka sorong, multitester, hand refracstometer, pH meter, pipa paralon (20cm), sieve net, alat tulis dan alumunium foil. Metode sampling menggunakan 3 transek dengan panjang 100 m ke arah laut dengan jarak antar transek yaitu 50 m, dengan transek kuadran 1 x 1 m dimulai dari titik 0 sampai 100 m. Analisis data yang digunakan dalam penelitian ini yaitu tutupan lamun, kelimpahan Strombus sp., serta analisis PCA (Principal Component Analysis) yang menghubungkan antar variabel kelimpahan siput gonggong, tutupan lamun, parameter fisika kimia perairan dan substrat. Jenis Strombus sp. yang dijumpai diantaranya Strombus urceus, Strombus canarium dan Strombus turturella. Jenis Strombus urceus memiliki nilai 4,3 ind/m2 kelimpahan yang tinggi dibandingkan dengan jenis Strombus sp. lain pada seluruh stasiun. Jenis Strombus canarium dan Strombus turturella banyak ditemukan pada tutupan lamun yang rendah serta berasosiasi dengan jenis lamun Halophila, Thalassia hemprichii dan Halodule uninervis, sedangkan jenis Strombus urceus banyak ditemukan pada tutupan lamun yang sedang dan padat serta berasosiasi positif dengan Enhalus acoroides, Thallasia hemprichi, Cymodocea rotundata.